Hydrocracies, Engineers and Power: Questioning Masculinities in Water*. Issue 2 (4th May 2017) - Zwarteveen, Margreet
ABSTRACT: Beginning with colonial times and continuing to the present, irrigation engineering has been and is an important site for the construction of gendered power and hegemonic masculinities. The strong connection between masculinities and professional irrigation cultures provides one possible explanation of why hydraulic bureaucracies are so resistant to change: it makes behaviours and codes of conduct that are learned seem natural. Taking inspiration from masculinity studies and from feminist studies of technology and organizations, this article proposes two possible lines of inquiry for critically disentangling how the irrigation profession becomes or is made masculine. The first is the feminist historical analysis of water bureaucracies, and the second is a critical ethnography of contemporary irrigation organizations. Such studies are needed both to create more space for women engineers in government water agencies and to contribute to unravelling important cultural aspects of water politics.